2022
DOI: 10.3390/w14071080
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Macroinvertebrate Diversity as Affected by the Construction of Inland Waterways along Montane Stretches of Two Rivers in China

Abstract: Building inland waterways affects the natural structure, formation, and extent of the riverbed and riparian zone. It alters the hydrology and sediment deposition conditions and hence damages the aquatic ecosystem. To address the effects of the construction of inland waterways on the riverine biome, benthic macroinvertebrate communities were compared at different building stages of inland waterways along a gradient of shipping traffic density at two montane rivers in China. The Shannon–Wiener diversity index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Studies of hydromorphological alterations in rivers and/or their impacts on biodiversity are numerous [33][34][35][36][37][38]; however, few papers explicitly deal with HMWBs and AWBs and use adapted assessment methodologies (e.g., [39]). For example, the Polish hydromorphological assessment methodology presented in Garbowski et al [23] does have lower score thresholds for AWBs, but it does not determine MEP or take into consideration mitigation measures, as we did in this study.…”
Section: Challenges In Assessing Hydromorphological Conditions Of Hmw...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of hydromorphological alterations in rivers and/or their impacts on biodiversity are numerous [33][34][35][36][37][38]; however, few papers explicitly deal with HMWBs and AWBs and use adapted assessment methodologies (e.g., [39]). For example, the Polish hydromorphological assessment methodology presented in Garbowski et al [23] does have lower score thresholds for AWBs, but it does not determine MEP or take into consideration mitigation measures, as we did in this study.…”
Section: Challenges In Assessing Hydromorphological Conditions Of Hmw...mentioning
confidence: 99%
“…To obtain a complete picture of ecosystem function and distinction of MEP sites, the results of this study should be combined with the results of biological monitoring in order to determine the response of biological communities at different levels of degradation [36,37]. In Croatia, a study on hydromorphological alterations of natural water bodies [54] showed that homogenization of the substrate is especially problematic for invertebrates.…”
Section: Impact Of Hydromorphological Modifications On Biological Qua...mentioning
confidence: 99%
“…The disturbances generated by anthropogenic activities on aquatic ecosystems are directly felt by the biological communities in place [24,25]. These include benthic macroinvertebrates, which are the most commonly used in biomonitoring of these ecosystems today because of their sedentary nature and, above all, their different levels of tolerance to environmental pollution [26][27][28].…”
Section: Introductionmentioning
confidence: 99%